Visual, Auditory, Read/Write and Kinesthetic (VARK) Model-Based Peer Teaching Approach - Beltran, Kennedy; Abonita, Abby; Brazal, Angela; Relente, Jamil; Relente, Jessa Mae; Urbana, Jasmin (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Peer teaching has been researched as an effective strategy to engage pupils and promote academic success. In this research study, we recommend a new approach on peer teaching and the purpose is to assess the integration of the VARK model within a peer-teaching framework designed for science subject. Survey and test questionnaires were administered to elementary learners specifically Grade 6 level and data collected were subjected to descriptive statistics and hypothesis testing. VARK model of Neil Fleming was employed to determine pupil’s learning preferences and the finding revealed that the multimodal learning preference- Visual and auditory was the most preferred among the pupils. Meanwhile, pupil’s learning preference was integrated within a peer-teaching framework through a developed activity. The results demonstrate that the implemented intervention may significantly affect the learning acquisition of the pupils. Therefore, tailoring instructional strategies to students’ preferred learning styles can lead to improved learning outcomes, as revealed by the positive influence of the peer-teaching approach on the pupil’s performance. The findings of this study provide practical insights and recommendations that suggest further method to investigate long term impact of the proposed peer-teaching approach.